ANALYSIS OF LANGUAGE ERRORS IN THE VIDEO OF PRESIDENT JOKO WIDODO’S OFFICIAL SPEECH ON YOUTUBE IN 2019 - Senjaya, Sonia; Mulyaningsih, Indrya; Khuzaemah, Emah (ppjbsip, 2021)
This research aims to describe the form of language errors, namely pronunciation, and dictionerrors. This type of research is qualitative using a qualitative descriptive method. The technique used in data collection is to listen to the advanced technique, be free to engage in conversation, and take notes. The data collection instruments in this study were using data cards, documentation, and questionnaires. The data in this research are in the form of words from the pronunciation of President Joko Widodo and the source of this research data comes from the video of President Joko Widodo’s speech on Youtube. The data validity technique usestriangulation of methods and theories. The data is confirmed to be the same even though using different methods. In addition, the data was checked based on phonological theory. The data were analyzed using the agih method, with the determinant of the relevant language being the target object of the research. The steps taken when analyzing data are data collection, data reduction, data presentation, and conclusions. The results of this study, namely language errors in the pronunciation field in the video of President Joko Widodo’s official speech on Youtube in 2019, there were pronunciation errors due to phoneme changes, omission, and addition. Errors the level of diction, namely in the use or choice of words that are not correct. Tahus, the results of this study are implemented in Indonesian language learning in junior high school class IX. AbstrakPenelitian ini bertujuan untuk mendeskripsikan bentuk kesalahan berbahasa, yakni pada kesalahan pelafalan dan diksi. Jenis penelitian ini adalah kualitatif dengan menggunakan metode deskriptif kualitatif. Teknik yang digunakan dalam pengumpulan data yaitu simak dengan teknik lanjutan bebas libat cakap dan catat. Instrumen pengumpulan data pada penelitian ini dengan menggunakan kartu data, dokumentasi, dan angket. Data dalam penelitian ini berupa kata dari pelafalan Presiden Joko Widodo dan sumber data penelitian ini dari video pidato Presiden Joko Widodo di Youtube. Teknik keabsahan data menggunakan triangulasi metode dan teori. Data dipastikan sama meskipun dengan menggunakan metode yang berbeda. Selain itu, data dicek berdasarkan teori fonologi. Data dianalisis menggunakan metode agih, dengan alat penentu dari bahasa bersangkutan yang menjadi objek sasaran dari penelitian. Langkah-langkah yang ditempuh ketika menganalisis data adalah pengumpulan data, reduksi data, penyajian data, dan simpulan. Hasil penelitian ini yaitu: kesalahan berbahasa pada bidang pelafalan dalam video pidato resmi Presiden Joko Widodo di Youtube tahun 2019 terdapat kesalahan pelafalan karena perubahan, penghilangan, dan penambahan fonem. Kesalahan pada tataran diksi yakni pada penggunaan atau pemilihan kata yang tidak tepat.